Noun phrases from a receptive viewpoint. The relevance of treatment of a neglected category in learner grammars of German as a foreign language - Farhidnia, Arash (Kalbotyra, 2017)
The disposition of grammars for German as a foreign language is dominated by the grammar of the different parts of speech and sentence structure. This arrangement is oriented, at one side, towards the Duden grammar which, up to the sixth edition (1998), practically gives no own place to the phrase as an independent grammatical category; on the other side, it is influenced by the grammar of Helbig & Buscha (2001) in which, since it is a mixture of functional and valency grammar, the category phrase is disregarded. However, the exclusion of phrase as a grammatical category for its own suggests a direct transition from word to sentence and origins ultimately in the concept that a sentence consists of an ordered set of single words. But at the latest, when the conversation turns to the determination of sentence components, learners are confronted with precisely the quantity which is located between the level of the individual word and the sentence and which is, as concerns expandability and diversity, equal to the sentence. Moreover, the recognition of the sentence depends for long stretches on the recognition of the phrase structure. The following article aims (with reference to the discussion of complex noun phrases and their role in the formation of Garden-path- and similar structures) to draw attention on the importance of treatment of noun phrases from the linear point of view and to show some selected aspects which should be treated in learner grammars. It will be shown that the theming of phrase topology will be sufficient for promoting a better understanding of the parts of speech and thus will help the learner to receive (and maybe produce) highly complex structures in German.